Age-friendly cities and communities questionnaire: A research on Turkish validity and reliability - Ozer, Zulfunaz; Turan, Gulcan Bahcecioglu; Teke, Neslihan (Routledge Journals, Taylor & Francis Ltd, 2023)
Purpose This study has been conducted to test the Turkish Validity and Reliability of the Age-Friendly Cities and Communities Questionnaire. Materials and Methods This methodological research has been carried out in a health center in Istanbul between January and April 2021. Between the specified dates, 306 older adults who met the research criteria within the population of the research, who accepted to participate and returned the filled-out questionnaires have been included in the study. The items of the scale are scored between -2, 2 and the scale consists of 20 items and 8 sub-dimensions. After the scale was translated, the content and structure validity tests were carried out. Results As a result of the evaluations and analyses, the content validity index of the scale was found to be 0.96. In the explanatory factor analysis conducted in the adaptation of the scale to Turkish, the total variance rate explained was found to be 92.36%. The factor loads of all items ranged between 0.71 and 0.91. The Cronbach Alpha values of the sub-dimensions of the scale ranged from .899 to .969, and the total Cronbach Alpha value was determined as .954. EFA and CFA results showed that the scale consists of 8 sub-dimensions with 20 items and the factor structure is sufficient. Good coherence index values were obtained as a result of CFA. Conclusion The Turkish version of the Age-Friendly Cities and Communities Questionnaire is a valid and reliable measurement tool to evaluate age-friendly practices in an area where older adults live.
Keywords: Age-friendly city; older adult; reliability; validity